Забезпечення матеріальними ресурсами будівельного підприємства - Синиця, М. М. (Ways to Improve Construction Efficiency, 2014)
The article describes the main groups of material resources construction company. The sources of formation of financial resources of construction enterprises, as well as guidelines for their use. The basic indicators to measure the efficient use of material resources in the construction business.